Light exposure profiles differ between myopes and non-myopes outside school hours - John G Lawrenson; Rakhee Shah; Rohit Dhakal; Byki Huntjens; Pavan Kumar Verkicharla (BMJ Open Ophthalmology)
Purpose Considering the putative role of light in myopia, and variations in socioeconomic, lifestyle, educational and environmental factors across ethnicities, we objectively investigated light exposure patterns in Indian school children.Methods The light exposure profile of 143 school children (9–15 years, 50 myopes) recorded using a validated wearable light tracker for six continuous days was analysed. Additional data for non-school days were available for 87 children (26 myopes). The illuminance exposure levels, time spent outdoors and epoch (number of times participant is exposed to a predefined range of lux level per day) were compared between myopes and non-myopes across different light conditions: ≥1000, ≥3000, ≥5000 and ≥10 000 lux. For school days, light exposure profiles during (1) before school, school and after school hours; and (2) class, break and transition (when a student travels to and from school) time were analysed.Results The overall median (IQR) daily illuminance exposure level, time spent outdoors and epochs at outdoors (≥1000 lux) were 807 (507–1079) lux/day, 46 (30–64) min/day and 9 (6–12) times/day, respectively. The daily illuminance exposure on non-school days was significantly higher in non-myopes than myopes (6369 (4508–9112) vs 5623 (2616–6929) lux/day, p=0.04). During transition time (school days), non-myopes had significantly higher illuminance exposure (910 (388–1479) vs 550 (263–1098) lux/day, p=0.04), spent more time outdoors (25 (10–43) vs 14 (4–29) min/day, p=0.01) and had higher outdoor epochs (6 (4–11) vs 5 (2–8) times/day, p=0.01) than myopes.Conclusions A small but significant difference in illuminance exposure, time spent outdoors and epoch was noted between myopes and non-myopes during transition time, which may have implications in myopia control.